Mastering ASP.NET web API : build powerful HTTP services and make the most of the ASP.NET Core Web API platform - Pattankar, Mithun; Hurbuns, Malendra (Packt Publishing, 2017)
Leverage ASP.Net Web API to build professional web services and create powerful applications. About This Book Get a comprehensive analysis of the latest specification of ASP.NET Core and all the changes to the underlying platform that you need to know to make the most of the web API See an advanced coverage of ASP.NET Core Web API to create robust models for your data, create controllers, and handle routing and security This book is packed with key theoretical and practical concepts that can be instantly applied to build professional applications using API with Angular 4, Ionic, and React Who This Book Is For This book is for .Net developers who wants to Master ASP.NET Core (Web API) and have played around with previous ASP.NET Web API a little, but don't have in-depth knowledge of it. You need to know Visual Studio and C#, and have some HTML, CSS, and JavaScript knowledge. What You Will Learn Acquire conceptual and hands-on knowledge of ASP.NET Core (MVC Web API) Learn about HTTP methods, the structure of HTTP content, internet media types, and how servers respond to HTTP requests and their associated HTTP codes Explore middleware, filters, routing, and unit testing Optimize Web API implementations Develop a secure Web API interface Deploy Web API projects to various platforms Consume your web API in front end application based on Angular 4, Bootstrap, and Ionic Implement and explore the current trends in service architecture In Detail Microsoft has unified their main web development platforms. This unification will help develop web applications using various pieces of the ASP.NET platform that can be deployed on both Windows and LINUX. With ASP.NET Core (Web API), it will become easier than ever to build secure HTTP services that can be used from any client. Mastering ASP.NET Web API starts with the building blocks of the ASP.NET Core, then gradually moves on to implementing various HTTP routing strategies in the Web API. We then focus on the key components of building applications that employ the Web API, such as Kestrel, Middleware, Filters, Logging, Security, and Entity Framework. Readers will be introduced to take the TDD approach to write test cases along with the new Visual Studio 2017 live unit testing feature. They will also be introduced to integrate with the database using ORMs. Finally, we explore how the Web API can be consumed in a browser as well as by mobile applications by utilizing Angular 4, Ionic and ReactJS. By the end o ...